Ethnobotanical Awareness Level of Secondary School Students On Plants Specific to The Region They Live in - Günver, Tülin; Atıcı, Tahir (GLOBETS 2023 Educational Technology and Science Research, 2024)
This research aimed to determine the awareness levels of secondary school students about plants that have ethnobotanical value specific to the region they live in. An awareness scale was used to determine students' awareness of plants with ethnobotanical value specific to their region. When evaluating the data of the relevant scale, it is stated as percentage and frequency. When the data were examined, it was determined that the student's awareness levels of plants with ethnobotanical value specific to their region were very low. However, it was observed that the recognition levels of cranberry and hawthorn plants were high. It was determined that female students were familiar with more local plants than male students. Bu araştırmada, ortaöğretim öğrencilerinin yaşadıkları yöreye özgü etnobotanik değeri olan bitkilere farkındalık düzeylerinin belirlenmesi amaçlanmıştır. Öğrencilerin yörelerine özgü etnobotanik değeri olan bitkilere farkındalıklarının saptanması için, farkındalık ölçeği kullanılmıştır. İlgili ölçeğin verileri değerlendirilirken yüzde ve frekans olarak belirtilmiştir. Veriler incelendiğinde öğrencilerin yörelerine özgü etnobotanik değeri olan bitkilere farkındalık düzeylerinin çok düşük olduğu tespit edilmiştir. Ancak kızılcık ve alıç bitkilerini tanıma düzeylerinin yüksek olduğu görülmüştür. Kız Öğrencilerin erkek öğrencilere oranla daha fazla sayıda yöresel bitkileri tanıdıkları belirlenmiştir.